PERCERAIAN DALAM KELUARGA KRISTEN DAN PERKAWINAN LAGI DITINJAU DARI MATIUS 19 DAN PENCEGAHANNYA - Johanes Witoro (Jurnal Teologi Biblika, 2021)
The number of cases of divorce, causing the image of Christianity cannot show its duty as the light and salt of the world. This research was conducted with qualitative methodology with literature study (literature). In the Bible study of Matthew 19, it is stated that divorce is prohibited, it is permissible to divorce if there is adultery. After a study it is meant that divorce is permitted because of sin in the family, it is necessary to resolve the conflict. Considering the huge impact of divorce, it is necessary to solve and prevent strategies in the Christian family.